Religious Coping with Sexual Stigma in Young Adults with Same-Sex Attractions - Lauricella, Shauna K. (Journal of religion and health, 2017)
The present study assessed religious coping with sexual stigma in 260 young adults with same-sex attractions. Although the majority of the sample rarely utilized religious coping, a significant minority of participants frequently turned to religion to deal with sexual stigma. Controlling for demographic and general religious variables, positive religious coping (e.g., connecting with God) was associated with beneficial outcomes, and negative religious coping (e.g., frustrations with one’s spiritual community) related to poorer adjustment to sexual stigma. Data are presented on how religious coping varied as a function of religiosity and sexual identity development (e.g., disclosure of sexual orientation to others).